Ichneumonid parasitoids (Hymenoptera: Ichneumonidae) reared in North Europe from pupae of Chelis puengeleri (Bang-Haas, 1927) (Lepidoptera: Erebidae, Arctiinae) - Vikberg, Veli; Nupponen, Kari; Nupponen, Timo; Savolainen, Pekka; Tahvanainen, Kari; Tiittanen, Jukka; Riedel, Matthias (Entomologica Fennica, 2019)
Four ichneumonid species were reared for the first time from pupae of Chelis puengeleri in North Europe. One female of Pimpla sodalis Ruthe, 1859 (Pimplinae) was reared in Cievrracohkka, N Sweden in July 2012. One male of Ichneumon formosus Gravenhorst, 1829 (Ichneumoninae) was reared in Nissuntjårro, Torne Lappland, Sweden in July 2012. One male of Ichneumon vafer Tischbein, 1876 (Ichneumoninae) was reared in July 1999 in the Iremel Mountain reserve, Baskiria, South Ural, Russia. Two females and one male of Ichneumon holoarctiae Riedel et Vikberg sp. n. (Ichneumoninae) were reared in June and July 2004 and 2012 in Finnmark, North Norway.